International case studies in asset management - Lloyd, Chris, 1959- (ICE, 2012)
'International Case Studies in Asset Management' shows stakeholders at every level how an asset management approach can provide the strategic perspective, transparency, and tools they need to maximise returns on capital, grow market value, and demonstrate that investments are put to best use.